The evaluation of enhancing instructional media for writing ability on students’ descriptive text: An experimental study - Muhamad Taridi (Universitas Jambi, Magister Program of English Education Department, 2022)
The purpose of this research was to investigate the impact of animated cartoons as instructional material on students' descriptive text writing abilities. This study used the descriptive text to assess writing skills of 7th – grade students at one of Jambi City's junior high schools. In this study utilized the T-test and posttest and only control group design with samples of 32 participants in either the experimental or control groups. Then, calculating the greatest and lowest scores, the data range, separating the group, determining the gap, computing the deviation standard, and determining the standard deviation either cartoon or non-cartoon material versus the pupils' proficiency level. Confirming to this study, T obtained = 4.98 is significantly higher than Ttabel (2, 00 < 4, 98 ˃ 2, 65). It revealed a significant achievement when participants created words making use of detailed narration and animated cartoon material. Further research suggests that researchers examine descriptive text writing skills using pre- and post-test experiment designs or other designs involving a digitally animated cartoon.